Hak-Hak Penyandang Disabilitas dalam Proses Penyebarluasan dan Partisipasi Masyarakat dalam Pembentukan Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja - Violetta, Cicilia Alda; Susetyo, Heru (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
The dissemination and public participation process should be evenly distributed to every community group, including groups of Persons with Disabilities. It is because groups or organizations of persons with disabilities have never been considered and involved by the Government and the House of Representatives since the beginning of the draft of the Law of the Republic of Indonesia No. 11 of 2020 on Job Creation (Job Creation Law) discussion. The substance of the law is very relevant and will impact persons with disabilities. The non-participatory process of drafting the Job Creation Law stems from a non-transparent process characterized by the difficulty for the public to access documents related to the discussion of the law. The lack of public involvement, mainly of persons with disabilities, has also been the criticism target in forming this law. This research method is doctrinal. The results show that the rights of persons with disabilities in the process of dissemination and public participation have been regulated in the CRPD, this is also related to Meaningful participation, which should have been given by the government and the state to all people equally so that their aspirations can be expressed, but the fact does not reflect this, as the Job Creation Law which seems hasty and lack of public participation. Therefore, understanding the meaning of principles and implementing the applicable legal norms is needed to realize meaningful participation.